The Effect of Household Dependency Ratio on the Mental Health of Workforce: Evidence From China - Fang, Dongli (Frontiers in Public Health, 2022)
Based on the Chinese General Social Survey (CGSS) 2010, this article investigates the relationship between household dependency ratio and the mental health of household workforce. The empirical results verify the negative impacts of both household old-age dependency ratio and child dependency ratio on the mental health of the workforce and find that the negative effect of old-age dependency ratio is greater than that of child dependency ratio. Moreover, the depression source of the young workforce mainly comes from the child dependency ratio, while the depression source of the older workforce comes from the old-age dependency ratio. The mental health of the workforce in poor regions is impaired by the household dependency burden, but we found no same evidence in rich regions. The old-age dependency ratio negatively affects the mental health of the workforce due to the household healthcare burden, while the child dependency ratio negatively affects the mental health of the workforce due to the education expenditure pressure. Our findings provide evidence on how household structure affects the welfare of the family, and give implications to the improvement of residents' health.